Cotrimoxazole prophylaxis decreases tuberculosis risk among Asian patients with HIV. Issue 3 (29th March 2019) - Ku, Stephane Wen‐Wei; Jiamsakul, Awachana; Joshi, Kedar; Pasayan, Mark Kristoffer Ungos; Widhani, Alvina; Chaiwarith, Romanee; Kiertiburanakul, Sasisopin; Avihingsanon, Anchalee; Ly, Penh Sun; Kumarasamy, Nagalingeswaran; Do, Cuong D; Merati, Tuti P; et al.
Abstract: Introduction: Cotrimoxazole (CTX) is recommended as prophylaxis against Pneumocystis jiroveci pneumonia, malaria and other serious bacterial infections in HIV‐infected patients. Despite its in vitro activity against Mycobacterium tuberculosis, the effects of CTX preventive therapy on tuberculosis (TB) remain unclear. Methods: Adults living with HIV enrolled in a regional observational cohort in Asia who had initiated combination antiretroviral therapy (cART) were included in the analysis. Factors associated with new TB diagnoses after cohort entry and survival after cART initiation were analysed using Cox regression, stratified by site. Results: A total of 7355 patients from 12 countries enrolled into the cohort between 2003 and 2016 were included in the study. There were 368 reported cases of TB after cohort entry with an incidence rate of 0.99 per 100 person‐years (/100 pys). Multivariate analyses adjusted for viral load (VL), CD4 count, body mass index (BMI) and cART duration showed that CTX reduced the hazard for new TB infection by 28% (HR 0.72, 95% CI l 0.56, 0.93). Mortality after cART initiation was 0.85/100 pys, with a median follow‐up time of 4.63 years. Predictors of survival included age, female sex, hepatitis C co‐infection, TB diagnosis, HIV VL, CD4 count and BMI. Conclusions: CTX was associated with a reduction in the hazard for new TB infection but did not impact survival in our Asian cohort. The potential preventive effect of CTX against TB during periods of severe immunosuppression should be further explored.